2003
DOI: 10.1096/fj.02-1104fje
|View full text |Cite
|
Sign up to set email alerts
|

Dual oxidases represent novel hydrogen peroxide sources supporting mucosal surface host defense

Abstract: Lactoperoxidase (LPO) is an enzyme with antimicrobial properties present in saliva, milk, tears, and airway secretions. Although the formation of microbicidal oxidants by LPO has been recognized for some time, the source of hydrogen peroxide (H2O2) for LPO-catalyzed reactions remains unknown. Reactive oxygen species produced by the phagocyte NADPH oxidase (phox) play a critical role in host defense against pathogens; however, analogous oxidant-generating systems in other tissues have not been associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
448
3
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 449 publications
(492 citation statements)
references
References 32 publications
20
448
3
6
Order By: Relevance
“…Subsequent studies have shown that Duox enzymes are not restricted to the thyroid, but are also present in epithelial cells of the gastrointestinal and respiratory tract (27). The exact role of Duoxes at these sites is not completely understood but an antimicrobial function has been suggested by several studies (26).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have shown that Duox enzymes are not restricted to the thyroid, but are also present in epithelial cells of the gastrointestinal and respiratory tract (27). The exact role of Duoxes at these sites is not completely understood but an antimicrobial function has been suggested by several studies (26).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells in salivary ducts express Duox2, and those in trachea and bronchus express Duox1; these Duox enzymes are likely to play a role in humans as a source of H 2 O 2 for LPO-dependent antimicrobial activity [22]. Induction of Nox1 and other mucosal Nox enzymes by cytokines [23] and bacterial products [24] provides circumstantial evidence for a role for Nox/Duox enzymes in mucosal innate immunity, although it should also be noted that Nox1 is induced by a variety of other agonists including growth factors, consistent with other roles such as mitogenic regulation.…”
Section: Nox Enzymes and Mucosal Immunitymentioning
confidence: 99%
“…Analysis of total lung or airway mRNA revealed the presence of substantial amounts of NOX2 as well as DUOX1 and DUOX2, and low amounts of NOX1 and NOX4 (35,(79)(80)(81). Although expression of NOX originates primarily from alveolar macrophages and other inflammatory cell types, the other NOX/DUOX enzymes are largely expressed in non-phagocytic cells within the lung, including airway and alveolar epithelial cells, pulmonary endothelial cells, fibroblasts, and smooth muscle cells.…”
Section: Nox Isozymes Within the Respiratory Tractmentioning
confidence: 99%
“…The fact that ROS production by polarized epithelia occurred only apically and could be stimulated by activators of protein kinase C (82), known to activate the phagocyte NADPH oxidase (5), suggested regulated and compartmentalized epithelial ROS production by an NADPH oxidase. The source of epithelial ROS was identified only a few years ago, after initial discovery of prominent expression of the NOX homologs DUOX1 and DUOX2 within the lung (35), and studies on lung tissues using in situ hybridization and immunohistochemistry, which revealed the presence of DUOX1 at the apical surface of tracheobronchial epithelial cells, and DUOX2 within salivary and submucosal glands (19,79,83,84 (88,89), which is due to the presence of DUOX1 (90). Although DUOX expression in the lung is primarily localized to airway or alveolar epithelial cells, recent studies have also suggest the presence of DUOX proteins in lymphocytes (51,91).…”
Section: Nadph Oxidases Within the Airway Epithelium: Duox1 And Duox2mentioning
confidence: 99%